Review Essay: Recent Works in the Political Theory of Migration. Issue 1 (2023) - Sager, Alex
Abstract : Thirty-five years ago, Joseph Carens published "Aliens and Citizens: The Case for Open Borders" in the Review of Politics . It is only a slight overstatement to say that this article created the subfield of political theory of migration. Today, the field is flourishing. Migration continues to be one of today's most politically fraught and morally urgent issues. An estimated hundred million people have fled violence and persecution. Hundreds of millions more cross international borders every year. States have responded with highly restrictive policies, in which people need to resort to perilous routes, often in the hands of smugglers, to claim asylum.